140 Effects of heat stress during late gestation on the dam and its calf. (7th December 2018) - Tao, S; Dahl, G; Laporta, J; Bernard, J
Abstract: Heat stress during late gestation, such as the dry period between two successive lactations, negatively impacts the performance of the dam and its calf. This brief exposure of the adverse environment before parturition impacts the physiological responses, tissue development, metabolism and immune function of the dam and offspring, thereby limiting their productivity. During the dry period, heat stress blunts mammary involution by attenuating mammary autophagic activity, and reduces following mammary cell proliferation, leading to impaired milk production in the subsequent lactation. As a result, early lactating cows that experience prepartum heat stress display reduced adipose tissue mobilization and lower degree of insulin resistance on peripheral tissues. Similar to mammary gland development, the placental function is impaired by heat stress as evidenced by reduced secretions of placental hormones in late gestating cows, which explains the reduced fetal growth rate and lighter birth weight of the calves. Compared with those from cooled dams, calves born to heat-stressed dry cows maintain lower body weight until one year of age, but display a stronger ability to absorb glucose during metabolic challenges postnatally. Immunity of the calves, such as passive and cell-mediated immune function, is also reduced by prenatal heat stress, resulting in increased susceptibility of the calves to diseases in their postnatal life. In fact, calves that experience maternal heat stress during late gestation have reduced survival rate before puberty. Study also indicates that heifers born to late gestation heat-stressed cows have lower milk production during their first lactation, and emerging evidence suggest that the epigenetic modification on mammary gland development by maternal heat stress may be one of the mechanisms to mediate this effect.